Infective Endocarditis in the Elderly: Challenges and Strategies - Carlos Bea; Sara Vela; Sergio García-Blas; Jose-Angel Perez-Rivera; Pablo Díez-Villanueva; Ana Isabel de Gracia; Eladio Fuertes; Maria Rosa Oltra; Ana Ferrer; Andreu Belmonte; Enrique Santas; Mauricio Pellicer; et al. (Journal of Cardiovascular Development and Disease, 2022)
The specific management of infective endocarditis (IE) in elderly patients is not specifically addressed in recent guidelines despite its increasing incidence and high mortality in this population. The term “elderly” corresponds to different ages in the literature, but it is defined by considerable comorbidity and heterogeneity. Cancer incidence, specifically colorectal cancer, is increased in older patients with IE and impacts its outcome. Diagnosis of IE in elderly patients is challenging due to the atypical presentation of the disease and the lower performance of imaging studies. Enterococcal etiology is more frequent than in younger patients. Antibiotic treatment should prioritize diminishing adverse effects and drug interactions while maintaining the best efficacy, as surgical treatment is less commonly performed in this population due to the high surgical risk. The global assessment of elderly patients with IE, with particular attention to frailty and geriatric profiles, should be performed by multidisciplinary teams to improve disease management in this population.